STRATEGI BISNIS DAN KONSERVATISME AKUNTANSI TERHADAP KINERJA PERUSAHAAN - Della Nurmala Sari; Suwarno Suwarno (PROCEEDING UMSURABAYA, 2022)
ABSTRACT  This study aims to examine business strategy and accounting conservatism on company performance. The population used is manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sample of this study amounted to 42 pieces selected based on the purposive sampling technique. This study uses quantitative methods with secondary data sources incomplete company annual financial statements. This study indicates that business strategy affects company performance, while accounting conservatism does not affect company performance.Keywords                   :Business Strategy; Accounting Conservatism; Company Performance